Intraoperative Ultrasound Applications in Intracranial Surgery - Shores, Andy; Lee, Alison M.; Kornberg, S. T.; Tollefson, Chris; Seitz, Marc A.; Wills, R. W.; Beasley, Michaela J. (Frontiers in Veterinary Science, 2021)
The methods and use of intraoperative ultrasound in 33 canine and five feline patients and its ability to localize and identify anatomical structures and pathological lesions in canines and felines undergoing intracranial surgery are described from a case series. All were client-owned referral patients admitted for neurologic evaluation, with an advanced imaging diagnosis of an intracranial lesion, and underwent surgical biopsy or surgical removal of the lesion. Medical records, retrieval and review of imaging reports, and characterization of findings for all canine and feline patients show that intraoperative ultrasound guidance was used in intracranial procedures during the period of 2012 and 2019. Twenty-nine of the canine patients had intracranial tumors. The remainder had various other conditions requiring intracranial intervention. Three of the feline patients had meningiomas, one had a depressed skull fracture, and one had an epidural hematoma. The tumors appeared hyperechoic on intraoperative ultrasound with the exception of cystic portions of the masses and correlated with the size and location seen on advanced imaging. Statistical comparison of the size of images seen on ultrasound and on MRI for 20 of the canine tumors revealed no statistical differences. Neuroanatomical structures, including vascular components, were easily identified, and tumor images correlated well with preoperative advanced imaging. The authors conclude that intraoperative ultrasound is a valuable asset in intracranial mass removals and can augment surgical guidance in a variety of intracranial disorders that require surgery. This is the first known publication in veterinary surgery of using intraoperative ultrasound as a tool in the operating theater to identify, localize, and monitor the removal/biopsy of intracranial lesions in small animals undergoing craniotomy/craniectomy.